Thematic Of CLT Analysis in The Textbook Bahasa Inggris for The Eleventh Grade Students of Senior High Schools - Rahmadani, Fahrizal (Institut Agama ISlam Negeri Palangka Raya, 2021)
A teaching and learning process teachers need a good references to their own class in English subject. So the reasons of choosing the textbook entitled